Rheological properties of magnesium phosphate cement with different M/P ratios. (3rd May 2021) - Ma, Cong; Chen, Gege; Jiang, Zhengwu; Zhou, Haijun; Yao, Hao; Zhou, Rui; Ren, Weixin
Highlights: The effect of M/P ratio on the yield stress and plastic viscosity is almost consistent with each other. The best rheological behavior appears in the M/P ratio of 3:1 judged by the rheological parameters. Initial hydration rate affected by M/P ratios is the dominant factor for rheological properties of MPC. Abstract: Magnesium phosphate cement (MPC) with unique advantages of quick setting and high early-strength has been used as grouting materials. The rheological properties of MPC, being vitally important for site operation, need to be studied further. Dead burnt magnesia (MgO) and phosphate (ADP) are the main raw materials for preparing MPC. This study measured the rheological properties with different M/P ratios, and the mechanisms of M/P ratio were studied by characterizing the zeta potential, 1 H NMR relaxation signal, water film thickness, mineral changes and electrical impedance. Experimental results indicate that both the yield stress ( τ0 ) and plastic viscosity ( η ) decrease firstly and then increase gradually with increasing the M/P ratio from 2.5:1 to 4.5:1. Higher M/P ratio decreases the interparticle water film thickness and accelerates the initial hydration rate remarkably, which is responsible for the change in rheological parameters. Low field NMR, TG-DTG analysis and Nyquist plots confirm the quicker initial hydration in MPC with higher M/P ratio. The change in hydration products is very slight during the rheological property measurements. Nyquist plots show that the MPC paste with lower M/P ratios has more compact microstructure and lower porosity at several hours. In a word, initial hydration rate is the most important factor influencing the rheological properties of MPC, and the separation distance among solid particles is the secondary factor.